Ökonomische Analyse der Arzt-Patient-Beziehung: Theoretische Modellierung und empirische Ergebnisse - Udo Schneider (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 2001)
– The paper reviews models of the physician-patient relationship to derive testable hypotheses about the relation between health, demand for medical services and patient's compliance. The models imply that in addition to existing information asymmetries the actions that physician and patient choose affect the results of medical care. We estimate an orderd probit model using German micro data and apply the empirical model to different samples. The key results are that the demand for medical care has a negative impact on the self-related health and that neighbourhood and environmental conditions have an impact too. Furthermore, patient's compliance positively affects the self-related health and in most cases, labour conditions are not significant with respect to individual's health.
Keywords: I11; D82; C25; 330; Arzt-Patient-Beziehung; Principal-Agent-Theorie; Ordered Probit-Schätzung; Gesundheitsökonomik; Prinzipal-Agent-Theorie; Ärzte; Kunden; Theorie; Schätzung; Deutschland